A fish bradykinin (Arg0; Trp5; Leu8-bradykinin) from the defensive skin secretion of the European edible frog; Pelophylax kl. esculentus: structural characterization; molecular cloning of skin kininogen cDNA and pharmacological effects on mammalian smooth muscle - Chen, X.; Wang, Lei; Wang, H.; Chen, H.; Zhou, Mei; Chen, Tianbao; Shaw, Christopher (Peptides, 2011)
Extensive studies on bradykinin-related peptides (BRPs) generated from plasma kininogens in representative species of various vertebrate taxa, have confirmed that many amphibian skin BRPs reflect those present in putative vertebrate predators. For example, the (Val1, Thr6)-bradykinin, present in the defensive skin secretions of many ranids and phyllomedusines, can be generated from plasma kininogens in colubrid snakes - common predators of these frogs. Here, we report the presence of (Arg0, Trp5, Leu8)-bradykinin in the skin secretion of the European edible frog, Pelophylax kl. esculentus, and have found it to be encoded in single copy by a kininogen with an open-reading frame of 68 amino acid residues. This peptide is the archetypal bony fish bradykinin that has been generated from plasma kininogens of the bowfin (Amia calva), the long-nosed gar (Lepisosteus oseus) and the rainbow trout (Onchorhynchus mykiss). More recently, this peptide has been shown to be encoded within cloned kininogens of the Atlantic cod (Gadus morhua) spotted wolf-fish (Anarichas minor), zebrafish (Danio rerio), pufferfish (Tetraodon nigroviridis) and Northern pike (Esox lucius). The latter species is regarded as a major predator of P. kl. esculentus. Synthetic (Arg0, Trp5, Leu8)-bradykinin was previously reported as having multiphasic effects on arterial blood pressure in conscious trout and here we have demonstrated that it can antagonize the relaxation in rat arterial smooth muscle induced by canonical mammalian bradykinin. The discovery of (Arg0, Trp5, Leu8)-bradykinin in the defensive skin secretion of this amphibian completes the spectrum of vertebrate taxon-specific BRPs identified from this source.